Shared themes, different countries: Qur'anic interpretation in the Twentieth Century Indonesia and Egypt - Ismail, Norbani (Atlantis Press, 2017)
This paper studies the interpretations of the Qur'an in the twentieth century Indonesia and Egypt. It examines the interpretation of Hamka and of al-Sha'rawi on verses related to women's issues such as gender equality, polygamy, and modesty. The study analyses their use of various exegetical tools that enable them to use their interpretations on the issues to evoke and affirm spiritual consciousness, construct a Muslim identity, and to use them as a platform for social criticism. The study finds that despite their geographical distance, both tafsir works share similar embedded themes: creating awareness of one's religious identity, instilling spiritual-theological consciousness among the Muslims, and continuity of the legacy of exegetical tradition.